Abnormal time‐zero histology is predictive of kidney transplant outcomes. Issue 7 (26th April 2022) - Raza, Syed Sikandar; Agarwal, Gaurav; Anderson, Douglas; Deierhoi, Mark; Fatima, Huma; Hanaway, Michael; Locke, Jayme; MacLennan, Paul; Orandi, Babak; Young, Carlton; Mannon, Roslyn B.; Seifert, Michael E.
Abstract: Introduction: Time‐zero biopsies can detect donor‐derived lesions at the time of kidney transplantation, but their utility in predicting long‐term outcomes is unclear under the updated Kidney Allocation System. Methods: We conducted a single‐center retrospective cohort study of 272 consecutive post‐reperfusion time‐zero biopsies. We tested the hypothesis that abnormal time‐zero histology is a strong indicator of donor quality that increases the precision of the kidney donor profile index (KDPI) score to predict long‐term outcomes. Results: We detected abnormal biopsies in 42% of the cohort, which were independently associated with a 1.2‐fold increased hazard for a composite of acute rejection, allograft failure, and death after adjusting for clinical characteristics including KDPI. By Kaplan‐Meier analysis, the relationship between abnormal time‐zero histology and the composite endpoint was only significant in the subgroup of deceased donor kidney transplants with KDPI scores >35. Abnormal time‐zero histology, particularly vascular intimal fibrosis and arteriolar hyalinosis scores, was independently associated with lower 12‐month estimated GFR. Conclusion: In conclusion, abnormal time‐zero histology is relatively common and identifies a group of kidney recipients at increased risk for worse long‐term outcomes. Further studies are needed to determine the optimal patient population in which to deploy time‐zero biopsies as an additional surveillance tool.